Sailing from Polis to Empire: Ships in the Eastern Mediterranean during the Hellenistic Period: edited by Emmanuel Nantet, Cambridge, England, UK, Open Book Publishers, 2020, 150pp., 48 illustrations, some colour, £27.95 (hbk) ISBN 978-1783746941, £17.95 (sbk) ISBN 978-1783746934, £5.99 (ebk) - Nakas, Ioannis (International Journal of Nautical Archaeology, 2022)
The next chapter, by Martin Galinier and Emmanuel Nantet, focuses on the largely unexplored subject of ancient ship construction, the work of ship-painters who, according to written sources, were specialists in decorating ships, probably with the encaustic technique, some launching successful careers as artists afterwards. Another major issue, left largely untouched by modern scholarship, is the development of ship technology during the period. Sailing from Polis to Empire: Ships in the Eastern Mediterranean during the Hellenistic Period: edited by Emmanuel Nantet, Cambridge, England, UK, Open Book Publishers, 2020, 150pp., 48 illustrations, some colour, £27.95 (hbk) ISBN 978-1783746941, £17.95 (sbk) ISBN 978-1783746934, £5.99 (ebk).